1994
DOI: 10.1002/tea.3660310405
|View full text |Cite
|
Sign up to set email alerts
|

Literacy learning in secondary school science classrooms: A cross‐case analysis of three qualitative studies

Abstract: The purpose of this cross‐case analysis is to illustrate how and why literacy was incorporated into science teaching and learning in three secondary classrooms. Research questions guiding the analysis include: (a) How were literacy events shaped by the teachers' philosophies about teaching science content and teaching students? and (b) How was literacy (reading, writing, and oral language) structured by the teachers and manifested in science lessons? The methodology of ethnography and the theoretical framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
12

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 19 publications
0
22
0
12
Order By: Relevance
“…With respect to the relationship between conceptions on the nature of science and conceptions on teaching and learning, for Brickhouse (1990), a teacher's conception of how scientific knowledge is constructed is consistent with his or her beliefs about how students learn science. Other work, however, has found discrepancies between the two (Carvajal & Gómez, 2002;Powell, 1994), and there is a greater consistency in experienced teachers than in novice or prospective teachers (Brickhouse, 1990;Dillon, O'Brien, Moje, & Stewart, 1994;Mellado, 1996;Tobin & Espinet, 1989).…”
Section: Science Teachers' Conceptionsmentioning
confidence: 96%
“…With respect to the relationship between conceptions on the nature of science and conceptions on teaching and learning, for Brickhouse (1990), a teacher's conception of how scientific knowledge is constructed is consistent with his or her beliefs about how students learn science. Other work, however, has found discrepancies between the two (Carvajal & Gómez, 2002;Powell, 1994), and there is a greater consistency in experienced teachers than in novice or prospective teachers (Brickhouse, 1990;Dillon, O'Brien, Moje, & Stewart, 1994;Mellado, 1996;Tobin & Espinet, 1989).…”
Section: Science Teachers' Conceptionsmentioning
confidence: 96%
“…Los escasos trabajos encontrados centran su atención en las relaciones entre las creencias del profesorado sobre la enseñanza y aprendizaje de las ciencias con su conducta en el aula al enseñar ciencias (Dillon, O'Brien, Moje, & Stewart, 1994;Lorsbach, Tobin, Briscoe, & LaMaster, 1992); en ellos, se encuentran evidentes contradicciones entre creencias explícitas y comportamiento. Este parece más bien matizado por el conjunto de valores, sentimientos, pensamientos y acciones formadas durante sus experiencias como estudiantes (Huibretse, Korthagen & Wubbels, 1994).…”
Section: Capítulo 2: El Desarrollo Profesional Docente Y Factores Queunclassified
“…Examples include Dillon et al (1994), Moje (1994), and Stewart (1989/90), all of whom studied high school science teachers and found that uses of literacy were connected to the teachers' instructional philosophies. In an earlier study, Hinchman (1985) compared a middle school social studies teacher, a high school science teacher, and a high school English teacher.…”
Section: Secondary Literacy Practices and Influencesmentioning
confidence: 99%
“…Reasons for this resistance remain unclear, however. Teachers' "local knowledge" of constraints and opportunities within the school setting is often unknown to those outside the school culture (O'Brien, 1988), and research has only begun to provide insights into beliefs secondary teachers hold about teaching and learning, how these beliefs develop over time, and how they affect classroom uses of literacy (Alvermann & Moore, 1991;Dillon, O'Brien, Moje, & Stewart, 1994). In essence, although understanding instruction from the teachers' perspective would seem necessary to the success of any educational reform effort (Moje, 1993), this perspective often has been ignored by researchers.…”
Section: R Eports On High School Instruction In the United States Indmentioning
confidence: 99%